Applicability of the GAIA Maternal and Neonatal Outcome Case Definitions for the Evaluation of Adverse Events Following Vaccination in Pregnancy in High-income Countries. Issue 12 (December 2021) - Watson, Gabriella; Dodd, Caitlin; Munoz, Flor M.; Eckert, Linda O.; Jones, Christine E.; Buttery, Jim P.; Yildirim, Inci B.; Kachikis, Alisa; Heath, Paul T.; Schlaudecker, Elizabeth P.; Bond, Nanette H.; Santarcangelo, Patricia L.; et al.
Abstract : Background: The Brighton Collaboration Global Alignment of Immunization Safety in Pregnancy (GAIA) project developed case definitions for the assessment of adverse events in mothers and infants following maternal immunization. This study evaluated the applicability of these definitions to data collected in routine clinical care and research trial records across 7 sites in high-resource settings. Methods: Data collection forms were designed and used to retrospectively abstract the key elements of the GAIA definitions from records for 5 neonatal and 5 maternal outcomes, as well as gestational age. Level of diagnostic certainty was assessed by the data abstractor and an independent clinician, and then verified by Automated Brighton Case logic. The ability to assign a level of diagnostic certainty for each outcome and the positive predictive value (PPV) for their respective ICD-10 codes were evaluated. Results: Data from 1248 case records were abstracted: 624 neonatal and 622 maternal. Neonatal outcomes were most likely to be assessable and assigned by the level of diagnostic certainty. PPV for preterm birth, low birth weight, small for gestational age and respiratory distress were all above 75%. Maternal outcomes for preeclampsia and fetal growth restriction showed PPV over 80%. However, microcephaly (neonatal outcome) and dysfunctional labor (maternal outcome) were often nonassessable, with low PPVs. Conclusions: The applicability of GAIA case definitions to retrospectively ascertain and classify maternal and neonatal outcomes was variable among sites in high-resource settings. The implementation of the case definitions is largely dependent on the type and quality of documentation in clinical and research records in both high- and low-resource settings. While designed for use in the prospective evaluation of maternal vaccine safety, the GAIA case definitions would likely need to be specifically adapted for observational studies using alternative sources of data, linking various data sources and allowing flexibility in the ascertainment of the elements and levels of certainty of the case definition. Abstract : Supplemental Digital Content is available in the text.